Modelo geolocalizado para conservação de estradas não pavimentadas - Moreira, Alisson Neves Harmyans (2018)
Unpaved roads are important access routes to urban centers, serving to facilitate the traffic of vehicles for socioeconomic purposes. In order to ensure the flow of goods produced and the transport of people, it is necessary that this road network has adaptations in order to prevent them from becoming channels and, consequently, erosion processes. In this sense, it is necessary to elaborate planning practices for the conservation of these roads. By means of field surveys and geomorphological databases, this study aimed to recommend and quantify the drainage devices for the sub-basin of the Olaria stream with the aid of a Geographic Information System (GIS), as well as to compare these with recommended devices from the Estradas model. The drainage devices used in the study were energy drains in the drainage channel and energy dissipaters in ditches. The recommendation of the drainage devices through the GIS were from geomorphometric and soil matrix databases. These data support the modeling, together with the geometric elements of the roads and the physical-water data of the soils of the beds and adjacencies. It was used data of reliefs from the image of the Topodata project, with accuracy and vertical precision of 5,529 m and 2,217 m, respectively. These results met the Class A Cartographic Accuracy Standard (PEC) for the representation of altimetric data in the 1:50.000 scale. Regarding the morphometric data of the segments, 90% of the slopes were compatible between the reference values of the GPS Geodesic receiver and the tested values of Topodata, thus obtaining the same recommendations for spines with water outlets. For the 50.1 km of unpaved roads in the subbasin of the Olaria stream, the GIS showed that only 12.1% of the segments did not require springs with water exits. It was recommended 953 water bars with outlets and 83 energy dissipaters in ditches. It was noted that the incompatibilities in the recommendations are related to the variables involved. Therefore, the geometric tracing and the excessive recommendations of these drainage devices by the GIS show that criteria such as relief and the soils were ignored in the implantation of the unpaved roads.